Assessment of mutagenic and antimutagenic effects of Punica granatum against ifosfamide induced chromosomal aberrations in male albino mice - Yaseen, Natheer J. (Iraqi Journal of Cancer and Medical Genetics, 2014)
The present study has been done to assess the mutagenic and antimutagenic effects of Punica granatum (Pomegranate) seed extract against the genotoxic effects ifosfamide (IFO) in male albino mice Mus musculus of BALB/c strain. The pomegranate seed extract (tablets) was provided by Source naturals, INC. Santa Cruse Company, Canada (from Egypt). Two independent experiments were performed. In the first, mice was treated daily and orally with phosphate buffer saline (PBS) as negative control group, and the other three groups were treated daily and orally with three different doses of the P. granatum seed extract (12.5, 25, and 50 mg/kg b.w.) for five weeks in order to test the clastogenetic effects of the plant seed extract. In the second experiment, the first group was positive control group which weekly and intraperitonially was treated with ifosfamide (100 mg/kg b.w.), the other three groups were treated daily and orally with three different doses of the pomegranate seed extract (12.5, 25, and 50 mg/kg b.w.) and also intraperitonially treated at the end of each week with IFO for five weeks to test the protective effects P. granatum seed extract. The results of the first experiment indicated that the P. granatum seed extract has no significant clastogenetic effects on chromosomal aberrations of the bone marrow cells of treated mice. The results of the second experiment was that the P. granatum seed extract, especially at the third dose (50 mg/kg b.w.) exhibited well protective and anti-clastogenetic effect against the genotoxic actions of the ifosfamide on bone marrow cells